Respuestas
Respuesta dada por:
6
-4x - 4y = 30
4x + 5y = -44 despejando 4x = - 44 - 5y
sustituyendo en la primera ecuación
- (-44 - 5y) - 4y = 30
44 + 5y - 4y = 30
y = - 14
reemplazando
4x = -44 - 5(-14)
4x = -44 + 70
4x = 26
x = 26/4
x = 6.5
4x + 5y = -44 despejando 4x = - 44 - 5y
sustituyendo en la primera ecuación
- (-44 - 5y) - 4y = 30
44 + 5y - 4y = 30
y = - 14
reemplazando
4x = -44 - 5(-14)
4x = -44 + 70
4x = 26
x = 26/4
x = 6.5
Preguntas similares
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años